Pengembangan media komik digital berbasis kearifan lokal berbantuan model pembelajaran picture and picture untuk meningkatkan kemampuan literasi membaca Sekolah Dasar - Nina Silvia; Ika Mustika; Muhammad Rizal Fauzi (COLLASE (Creative of Learning Students Elementary Education), 2026)
Abstract The goal of this project is to create digital comic media based on likal knowledge with the help of picture and picture learning model ini order to improve the reading literacy skills of elementary school studen. This study used modified version of Borg and Gall’s research and develompment method there are eight stage the study used a modified version thrid grade students in elementary schools in wes Bandung Regency and Cimahi city, Used Questionnaires and reading literacy assessment. Because the efficacy test in the restricted test showed a significant difference between the pretest and postest results (p<0.05), the findins are supported by expert validation with a median percentage of 92% and a material experct percentage of 95%. In the board exam utilisting the Man-Whitney test, there was No. significant difference between the experimental and control classes (P>0.05), despire the experimental class having a higher average value. Therefore the digital comic medium that was developed base on lokal knowledge may iimprove student’s literacy skills Keywords: Digital comics, Reading literacy, Picture and picture. Abstrak Tujuan pengembangan ialah membuat media komik digital dengan didasarkan pada basis kearifan lokal dengan bantuan model pembelajaran picture and picture untuk meningkatkan kemampuan literasi membaca di sekolah dasar. Metode research and development (R&D) yang di modifikasi dari metode Borg and Gall, digunakan dalam penelitian ini dengan 8 tahap metode. siswa kelas III di sekolah dasar negeri di Kabupaten Bandung Barat dan Kota Cimahi adalah subjek penelitian ini. Hasil tersebut divalidasi oleh para ahli dengan media 92% dan materi 95%, selanjutnya karena p<0.05, uji evektivitas pada uji terbatas memperlihatkan bahwa ada perbedaan antara pretest dan postest karena (p<.05). Namun pada uji luas menggunakan Man-Whitney, nilai rata-rata kelas eksperimen lebih tinggi dari kelas kontrol. Sehingga media komik digital dapat meningkatkan kemampuan literasi siswa. Kata Kunci: Komik digital, Literasi membaca, Picture and picture